MENINGKATKAN HASIL BELAJAR PKn MELALUI PENERAPAN METODE TANYA JAWAB DENGAN FARIASI MEDIA PEMBELAJARAN PADA POKOK BAHASAN MASYARAKAT MADANI DI KELAS XI IPS1 SMA NEGERI 10 PEKANBARU: (Improving PKn Subject Result of the Capital Method trough Questions and Answer by Using Learning Variative Media on the Topic of the Community Society in Class XI IPS1 SMA Negeri 10 Pekanbaru) - Darmali Darmali (UIR Press, 2017)
This research is based on the low percentage of achievement on the MinimumExhaustiveness Criteria that was given by the students of grade XI 1 SOCIAL 10SENIOR HIGH SCHOOL Pekanbaru, school year 2015/2016 From the number ofstudents 42 people who took the post test on the teaching materials Characteristic ofcivil society with Cooperative learning model, only 15 people can be passed (36.%)and the rest about 27 people are declared not graduated (64,%). The data indicate thatthe learning outcomes in these teaching materials can be declared unfinished. Thedisagreement is evident from the proof of the percentage of all students graduationonly reached 36,%. The percentage is far from the ideal percentage between 80% -100%. Even the percentage of graduation is smaller than the percentage of nongraduation.Therefore, for such cases it is necessary to hold a classical remedial. Theprocess of classical remedial in this case the author did through classroom actionresearch activities.